The Effect of Preheating on Fissure Sealant Viscosity - Ebru Hazar Bodrumlu; İ. Sefa Çakır (Current Research in Dental Sciences)
Objective: Fissure sealant application is used for the prevention of caries. The viscosity of the fissure sealant directly affects the retention of the material to the tooth. Heating resin-containing materials before polymerization decrease the viscosity of the material. The purpose of this study was to examine the fluidity levels of four different fissure sealants containing resin with different filling ratios at different temperatures before polymerization and to evaluate the obtained data by comparing them.Methods: The study of four different fissure sealant materials with resin content with different filler ratios (0%, 30%, 55%, and 70%) were heated at different temperatures (4ºC, 23ºC, 39ºC, and 55ºC) before polymerization. With the fluidity measurement between the two glasses, 20 fluidity measurement values were obtained at each temperature value, and a total of 320 measurements were made. The data were statistically evaluated with a two-way robust ANOVA analysis. Results: The study it was determined that the fluidity values of the fissure sealants increased with the heating process before polymerization. The best result in terms of fluidity in the fissure sealants without filler was obtained at a temperature of at least 23ºC. In the fissure sealants containing 30% and 55% filler, there was a significant difference in fluidity values when the temperature difference was large. Conclusion: It is thought that the filling ratio and temperature affect the fluidity in fissure sealants and that the appropriate temperature should be selected by considering the filling ratios to obtain the best result in terms of fluidity.Keywords: fluidity, viscosity, preheating, fissure sealant, the heating device.